OP303 Do You Get The Message? Making HTA Findings Easier For Decision-Makers To Implement. (December 2021) - Kandulu, Jess; Clifton, Ed; Robertson, Iain; Smart, Neil; Macpherson, Karen
Abstract : Introduction: Often health technology assessment (HTA) products developed by the Scottish Health Technologies Group (SHTG) did not reach clear directive conclusions because the evidence base for a technology was weak. Despite being methodologically robust, these products did not meet the needs of decision-makers and may have had negligible impact. Methods: SHTG set out to equip and empower the recommendation-making council (that is, appraisal committee) to reach clear conclusions. SHTG broadened the HTA components and types of evidence that could be considered. The increased breadth of evidence included: clinicians attending council meetings to respond to questions; patient groups making submissions and presenting at council meetings; Scotland-specific economic modelling; and consultation on draft recommendations. SHTG also restructured the council for improved deliberative decision-making. Results: Clear directive conclusions were reached in a substantially higher proportion of HTA products (eighty-eight percent in 2019 compared with eight percent in 2017). It became possible for decision-makers to implement findings. It also became feasible to assess the impact and implementation of recommendations. Conclusions: Broadening SHTG's consideration of HTA components has led to a clearer conclusion being reached and stronger messaging for decision makers. This positions SHTG to increase its influence in the use of health technologies in Scotland.